Tool development based on modelling and simulation of hot sheet metal forming of Ti-6Al-4V titanium alloy - Odenberger, E. -L.; Oldenburg, M.; Thilderkvist, P.; Stöhr, Thomas; Lechler, Jürgen; Merklein, Marion (Journal of Materials Processing Technology, 2011)
In the aero engine industry alternative manufacturing processes for load carrying aero engine structures imply fabrication. The concept of fabrication involves simple forgings, sheet metals and small ingots of e.g. titanium alloys which are welded together and heat treated. In the concept phase of the product development process, accurate evaluations of candidate manufacturing processes with short lead times are crucial. In the design of sheet metal forming processes, the manual die try out of deep drawing tools is traditionally a time consuming, expensive and inexact process. The present work investigates the possibility to design hot forming tools, with acceptable accuracy at short lead times and with minimal need for the costly die try out, using finite element (FE) analyses of hot sheet metal forming in the titanium alloy Ti-6Al-4V. A rather straightforward and inexpensive approach of material modelling and methods for material characterisation are chosen, suitable for early evaluations in the concept phase. Numerical predictions of punch force, draw-in and shape deviation are compared with data from separate forming experiments performed at moderately elevated temperatures. The computed responses show promising agreement with experimental measurements and the predicted shape deviation is within the sheet thickness when applying an anisotropic yield criterion. Solutions for the hot forming tool concept regarding heating and regulation, insulation, blank holding and tool material selection are evaluated within the present work. © 2011 Elsevier B.V. All rights reserved.
LFT Import::2019-07-29 (1690)
Keywords: FEM simulation; Hot forming test; Hot sheet metal forming; Ti-6Al-4V; Titanium alloys; Validation